2006
DOI: 10.1001/archopht.124.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow–Derived Cells in Normal Human Corneal Stroma

Abstract: To examine the normal human corneal stroma for the presence of bone marrow-derived cells. Methods: Thirty-four corneas from donors aged 56 to 71 years were used. The stroma of the donor corneas was examined immunohistochemically by fluorescent microscopy. CD45-positive and-negative cells were separated from collagenase-digested stroma by magnetic beads, and the expression of toll-like receptor 4 was analyzed. Results: CD45-positive cells were mainly found in the anterior stroma of the central and paracentral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 28 publications
1
32
2
1
Order By: Relevance
“…For separation of CD45-positive and CD45-negative cells, the stroma from three to five corneas was processed simultaneously. The average number of CD45-positive cells per cornea was 10.5 Ϯ 0.9 ϫ 10 3 (mean Ϯ SD), as described elsewhere (1). Average BMC rate per isolated cells from corneal stroma was 91 Ϯ 7% (mean Ϯ SD; n ϭ 5) in our preliminary study.…”
Section: Donor Human Corneas and Isolation Of Cd45-positive And Cd45-supporting
confidence: 61%
See 2 more Smart Citations
“…For separation of CD45-positive and CD45-negative cells, the stroma from three to five corneas was processed simultaneously. The average number of CD45-positive cells per cornea was 10.5 Ϯ 0.9 ϫ 10 3 (mean Ϯ SD), as described elsewhere (1). Average BMC rate per isolated cells from corneal stroma was 91 Ϯ 7% (mean Ϯ SD; n ϭ 5) in our preliminary study.…”
Section: Donor Human Corneas and Isolation Of Cd45-positive And Cd45-supporting
confidence: 61%
“…H uman leukocyte Ag DR-positive bone marrow-derived cells (BMCs) 3 of the monocyte lineage, which include monocytes, macrophages, and dendritic cells, exist in the normal human corneal stroma (1). These cells are mainly distributed in the anterior stroma of the central and paracentral cornea as well as all stromal layers of the peripheral cornea and may play a role in the innate and adaptive immune responses (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some GFP(1) cells in the corneal stroma were not immunostained for Iba1 and their lineages were not determined. Some previous reports showed the existence of antigen presenting dendritic cells in normal murine and human cornea (Hamrah et al, 2003a,b;Nakamura et al, 2005;Yamagami et al, 2006). We failed to detect the signal of the dendritic cell marker CD11c.…”
Section: Discussioncontrasting
confidence: 61%
“…47,49,50 A picture now emerges of a stratified resident myeloid population in the human cornea, with major histocompatibility complex (MHC) II + /CD45 + bone marrow-derived cells present throughout all layers of the peripheral stroma, as well as in the anterior stroma of the central cornea. 51 Classification of cell surface markers has enabled cell lineage identification: myeloid-derived dendritic cells (DCs) are considered CD11c + , while monocyte-derived lineages, including LCs, are CD14 + . 52 Hamrah et al 53 observed that some murine DCs in the periphery of the anterior stroma also express MHC II, CD80, and CD86, but the DCs located in the centre present an immature, MHC II − CD80 − CD86 − phenotype until inflammation is induced.…”
Section: Innate Immune Cells In the Mammalian Corneamentioning
confidence: 99%